Performance of XFAST in the presence of code Doppler - TANG Xiao-mei; YONG Shao-wei; WANG Fei-xue (Tongxin xuebao)
The probability of detection and false alarm in XFAST（extended replica folding acquisition search technique） were introduced in the condition of code Doppler and deterioration of noise caused by replica folding.The simulation re-sults show that the model is correct,the equal signal to noise error is less than 0.5dB.The research is the academic base of XFAST parameter optimization and performance.When the extended replica folding number equal to 1,the model can be used to analyse other acquisition algorithm.